2014
DOI: 10.1128/aem.03330-13
|View full text |Cite
|
Sign up to set email alerts
|

The Third Replicon of Members of the Burkholderia cepacia Complex, Plasmid pC3, Plays a Role in Stress Tolerance

Abstract: The metabolically versatile Burkholderia cepacia complex (Bcc) occupies a variety of niches, including the plant rhizosphere and the cystic fibrosis lung (where it is often fatal to the patient). Bcc members have multipartite genomes, of which the third replicon, pC3 (previously chromosome 3), has been shown to be a nonessential megaplasmid which confers virulence and both antifungal and proteolytic activity on several strains. In this study, pC3 curing was extended to cover strains of 16 of the 17 members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 29 publications
(43 reference statements)
3
46
0
Order By: Relevance
“…To test this hypothesis, we used an established strategy to confirm the presence of the third replicon based on a PCR screen with primer pairs used sequentially and designed to anneal to the highly conserved region concerning its replication origin. 27 With the exception of IST4129, all the other isolates gave a positive PCR result for the presence of this megaplasmid with the first set of primers (repAFor and repARev) ( Supplementary Fig. 2A).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…To test this hypothesis, we used an established strategy to confirm the presence of the third replicon based on a PCR screen with primer pairs used sequentially and designed to anneal to the highly conserved region concerning its replication origin. 27 With the exception of IST4129, all the other isolates gave a positive PCR result for the presence of this megaplasmid with the first set of primers (repAFor and repARev) ( Supplementary Fig. 2A).…”
Section: Resultsmentioning
confidence: 94%
“…26 This result strongly suggests, for the first time, the in vivo loss of the nonessential virulence third replicon in B. cenocepacia. Based on previous studies 26,27 and in the screening performed in this work comprising the 39 isolates examined throughout this study plus 20 5 additional isolates from patients AB and AN, all of them found to have the third replicon, it is possible to conclude that the in vivo loss of this megaplasmid, although possible, is a rare event.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Bcc genome is large (nearly 8 Mb for Burkholderia cenocepacia H111) and consists of at least three replicons; these are chromosomes 1 and 2 and the megaplasmid pC3. pC3 was previously known as chromosome 3 but has been found to be nonessential in every Bcc strain investigated so far (9,10). The large Bcc genome size and multireplicon structure enable Bcc strains to thrive in a range of different niches, both agricultural and medical.…”
mentioning
confidence: 99%
“…The less-conserved secondary chromosome contains genes important for niche adaptation of individual Bcc strains, whereas megaplasmid pC3 has roles in virulence and antifungal activity in various Bcc species, which are, to various degrees, dependent on the strain (9,10). It has also been shown to be important for stress tolerance in B. cenocepacia H111 (10). A number of wellcharacterized genes and clusters contributing to these phenotypes are carried by pC3.…”
mentioning
confidence: 99%